2014
DOI: 10.5152/tjar.2014.96630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anaesthesia Methods for Regaining Daily Life Activities in Cesarean Patients

Abstract: Objective: Postpartum period is physically, socially and emotionally a difficult time for the parents and the baby to become a family. We tried to investigate how the anaesthesia method affects patients who underwent cesarean delivery, as a factor which also affects this period. Methods:Two hundred and six parturients, who underwent elective cesarean delivery in Celal Bayar University Hafsa Sultan Hospital were recruited for our study. After demographic data and anaesthesia methods were noted, an EQ-5D health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Consistent with our findings, Gursoy et al showed that neuraxial anesthesia enables patients to return to normal daily activities earlier than general anesthesia. Moreover, the EQ-5D general health score was higher 24 h after cesarean delivery with regional anesthesia compared to general anesthesia [26].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Gursoy et al showed that neuraxial anesthesia enables patients to return to normal daily activities earlier than general anesthesia. Moreover, the EQ-5D general health score was higher 24 h after cesarean delivery with regional anesthesia compared to general anesthesia [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, QoR scoring tools for this obstetric population are limited. Several scoring tools, including QoR-40 [ 4 ], QoR-15, [ 5 ] EuroQol-5D [ 6 ], and Short Form Health Survey [ 7 ], have been used to measure maternal recovery after CS, but they have not been validated in obstetric settings. In addition, these scoring tools do not include items such as neonatal care, which is necessary for discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our findings, Gursoy et al (2014) showed that neuraxial anesthesia enables patients to return to normal daily activities earlier than general anesthesia. Because, the mobility, self-care, and activities scores were higher 24 hours and one week after cesarean delivery with spinal anesthesia compared to general anesthesia [25].…”
Section: Resultsmentioning
confidence: 80%